2012
DOI: 10.1177/1464884912442286
|View full text |Cite
|
Sign up to set email alerts
|

A reality check: How journalists’ role perceptions impact their implementation of the objectivity norm

Abstract: Objectivity is a cornerstone in the journalistic profession. There is a widespread acknowledgement that a one-to-one representation of reality is not possible, and thus the norm must be interpreted by journalists in their daily work. Based on a journalist survey among Danish journalists (N = 2008) we find that journalists’ role perceptions have substantial explanatory power in regard to how journalists implement the objectivity norm. The objectivity norm pervades the news production process by guiding journali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 25 publications
2
86
1
8
Order By: Relevance
“…Patterson (1998, 27) called objectivity the "defining norm of modern journalism". Surveys all over the world found that journalists refer to objectivity as a very important criterion for quality journalism (e.g., Skovsgaard et al 2012;Weaver and Willnat 2012). Journalistic standards further prescribe the presentation of a rational debate where a diversity of points of view is included in the news (Ward 2015, 299), turning balance into one of the important dimensions of objectivity.…”
Section: Vox Pops Public Opinion and Balancementioning
confidence: 99%
“…Patterson (1998, 27) called objectivity the "defining norm of modern journalism". Surveys all over the world found that journalists refer to objectivity as a very important criterion for quality journalism (e.g., Skovsgaard et al 2012;Weaver and Willnat 2012). Journalistic standards further prescribe the presentation of a rational debate where a diversity of points of view is included in the news (Ward 2015, 299), turning balance into one of the important dimensions of objectivity.…”
Section: Vox Pops Public Opinion and Balancementioning
confidence: 99%
“…Hampton (2008) argues that the objectivity ideal emerged from Reuters and BBC but may be denied by commercial news outlets. Indeed, for journalists of tabloid newspapers, value judgments and subjectivity were clearly important in a Danish study (Skovsgaard et al, 2013). This study also reveals that role conceptions explain the implementation of the objectivity norm.…”
Section: Hypotheses: the Revenue Model And News Contentmentioning
confidence: 53%
“…In this author's professional journalistic experience, and based on the interviews with participants in this study, individual journalists try to mediate traditional notions of objectivity that suggest they should disengage themselves from their own emotions and opinions as they try to separate fact from value (Usher 2009: 217) with a more modern understanding of impartiality based on accuracy and fairness (Ward 2004). Skovsgaard et al (2013) note that the utility of objectivity has been challenged on several grounds including claims that it forces journalists to be detached from what and whom they are covering, which leads to debate about value judgements and the introduction of bias. In a disaster such as the Canterbury earthquake, journalists are likely to be placed in a position where they will reappraise their connection to the story and those they are writing about.…”
Section: Collective Traumamentioning
confidence: 99%